The compliance ecosystem: Integrating personal, social, and institutional factors in income tax compliance - Wijaya, Suparna; Daryatinnisa, Nisrina; Romadon, Rizki Sahrul; Zikri, Rifda Nisrina; Amelia, Sevina Nurul; Quinnita, Vania Patricia (WIM Solusi Prima, 2025)
This study aims to analyze the factors that influence individual taxpayer compliance on income tax revenue through a systematic literature review approach. Data were collected from 30 research articles published in nationally and internationally accredited journals between 2019-2024, using strict inclusion and exclusion criteria. The analysis results reveal that taxpayer compliance is influenced by two main factor groups: (1) internal factors, including understanding of tax regulations, tax awareness, intrinsic motivation, and taxpayer perceptions; and (2) external factors, comprising tax service quality, effectiveness of tax sanctions, tax socialization, and implementation of tax technology. The findings also reveal interactions between internal and external factors that synergistically affect taxpayer compliance levels. The theoretical implications enrich the understanding of tax compliance determinants within Indonesia's self-assessment system context, while practical implications provide recommendations for tax authorities to develop integrated strategies targeting improvements in both factor groups to enhance taxpayer compliance.